2018
DOI: 10.1002/cnr2.1138
|View full text |Cite
|
Sign up to set email alerts
|

Selective sharing: The impact of patterns of communication in young people experiencing maternal cancer

Abstract: Background: Adolescents that experience parental cancer can have significant difficulties and may be at a greater risk of emotional and behavioural problems; however, some studies have found that this experience can also be empowering and can promote positive growth. Open communication specifically has been associated with coping and less psychological distress in adolescents experiencing parental cancer.Aims: The aim of this study is to identify communication patterns in adolescents that faced maternal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
0
2
0
4
Order By: Relevance
“…Empathy is foremost a positive and beneficial trait; however, it may also have a detrimental aspect. In this study, adolescents refrained from expressing their own emotions and needs to avoid causing further distress (Rodriguez, 2018). This was an active demonstration of empathy, but could also put an adolescent's mental health and well-being in jeopardy as they were not accessing the supports they might have needed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Empathy is foremost a positive and beneficial trait; however, it may also have a detrimental aspect. In this study, adolescents refrained from expressing their own emotions and needs to avoid causing further distress (Rodriguez, 2018). This was an active demonstration of empathy, but could also put an adolescent's mental health and well-being in jeopardy as they were not accessing the supports they might have needed.…”
Section: Discussionmentioning
confidence: 93%
“…Previous research on adolescents experiencing maternal cancer found that adolescents struggled with the diagnosis of maternal illness and developed a sense of care towards their mothers, beyond needs and emotions assuming caring roles (Rodriguez et al, 2016). Adolescents were also careful and mindful of the impact that their communication could have on their ill mothers, with the purpose of avoiding unpleasant conversations and protecting each other (Rodriguez, 2018). These studies, although not identified as such, suggest empathy in adolescents whose mothers were diagnosed with non-terminal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Ebeveynler tanıyı çocuklarına açıklamakta zorlanmanın yanı sıra iletişim esnasındaki tepkileri ve duygularından da endişe duyarlar. Bu korkular ebeveynler ve çocukları arasında daha fazla iletişim engeline neden olur (Hailey et al, 2018;O'Neill et al, 2020;Rodriguez, 2019;Shands & Lewis, 2021). Ebeveyninde kanser hastalığı olan adolesanlar ile iletişimin önündeki engelleri değerlendiren bir çalışmada açık iletişiminin önündeki engeller arasında, annelerinin konuşamayacak durumda olmaları, korku, ailelerinden coğrafi olarak uzakta olma, daha önceki aile iletişim kalıpları ve teşhisten bu yana geçen süre yer almaktadır.…”
Section: Aile Rolleriunclassified
“…Ebeveyninde kanser hastalığı olan adolesanlar ile iletişimin önündeki engelleri değerlendiren bir çalışmada açık iletişiminin önündeki engeller arasında, annelerinin konuşamayacak durumda olmaları, korku, ailelerinden coğrafi olarak uzakta olma, daha önceki aile iletişim kalıpları ve teşhisten bu yana geçen süre yer almaktadır. Açık iletişimin faydaları arasında sevgiye, desteğe ve bilgiye erişimin yanı sıra duygularının doğrulanması ve daha iyi başa çıkma bulunmaktadır (Rodriguez, 2019)…”
Section: Aile Rolleriunclassified
See 1 more Smart Citation